2005
DOI: 10.1007/s00383-005-1581-8
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum nitric oxide metabolites in biliary atresia

Abstract: Biliary atresia (BA) remains one of the most intractable liver diseases in children. The aim of this study was to investigate the possible roles of nitric oxide (NO) in BA. Serum levels of nitrite and nitrate (NO production) were determined using a colorimetric method from 65 post-operative BA patients and 12 healthy children. The patients were categorized into two groups according to their jaundice status, and serum alanine aminotransferase (ALT, a marker for liver injury). Unpaired t tests were used. Data ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…In addition, a number of cellular inflammatory markers have been studied including CD14-positive macrophages which secrete a number of inflammatory cytokines into the periductular tissue when activated by endotoxin [21]. Molecules involved in inflammatory pathways including ICAM-1 [7], nitric oxide metabolites [22], interleukin-8 [23], and monocyte chemoattractant protein-1 [24] have been proposed to be involved in the pathophysiology of progressive liver fibrosis in BA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a number of cellular inflammatory markers have been studied including CD14-positive macrophages which secrete a number of inflammatory cytokines into the periductular tissue when activated by endotoxin [21]. Molecules involved in inflammatory pathways including ICAM-1 [7], nitric oxide metabolites [22], interleukin-8 [23], and monocyte chemoattractant protein-1 [24] have been proposed to be involved in the pathophysiology of progressive liver fibrosis in BA.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the significant direct cellular effect of NO with respect to hepatic injury concerns apoptosis 28 . Our previous studies also demonstrated that there is an elevation of systemic NO production (serum nitrites and nitrates) in post‐operative BA patients 16 . Therefore, possible implications of hepatic iNOS expression in the pathophysiology of liver injury in BA are obvious.…”
Section: Discussionmentioning
confidence: 95%
“…Although we do not believe that the roles of iNOS are identical in BA and primary biliary cirrhosis, they may share some resultant NO effects. In addition, our previous results show that there is an elevation in systemic NO production (serum nitrate and nitrite levels) in BA patients 16 . Interestingly, the elevated NO production is associated with serum alanine transaminase (ALT) levels, a marker for liver injury 16 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The reactive nitrogen intermediates were measured by Green's method, which involves adding 100 µL of Greiss' reagent to 100 µL of serum and reading absorbance at 550 nm using assessed using Olympus spectrophotometer. Nitric oxide was calculated from a NaNO2 standard curve indirectly (Vejchapipat et al, 2006).…”
Section: Creatine Kinase and Nitric Oxide Assaymentioning
confidence: 99%